Causal relationship between macro-economic indicators and funds unit prices behavior: evidence from Malaysian Islamic equity unit trust funds industry - Othman, Anwar Hasan Abdullah; Mydin Meera, Ahamed Kameel; Abd. Aziz, Hassanuddeen (World Academy of Science, Engineering and Technology (WASET), 2015)
In this study, attempt has been made to investigate the relationship specifically the causal relation between fund unit prices of Islamic equity unit trust fund which measure by fund NAV and the selected macro-economic variables of Malaysian economy by using VECM causality test and Granger causality test. Monthly data has been used from Jan, 2006 to Dec, 2012 for all the variables. The findings of the study showed that industrial production index, political election and financial crisis are the only variables having unidirectional causal relationship with fund unit price. However the global oil price is having bidirectional causality with fund NAV. Thus, it is concluded that the equity unit trust fund industry in Malaysia is an inefficient market with respect to the industrial production index, global oil prices, political election and financial crisis. However the market is approaching towards informational efficiency at least with respect to four macroeconomic variables, treasury bill rate, money supply, foreign exchange rate, and corruption index.